Impacts of sulfide exposure on juvenile Tor tambroides (Bleeker, 1854): behavioral responses and mortality - Azimah, Binti Apendi; Ling, Teck Yee; Nyanti, L.; Sim, Siong Fong; Grinang, Jongkar; Lee, Karen Suan Ping; Tonny, Anak Ganyai (BIOFLUX SRL, 2019)
Construction of hydroelectric reservoirs had been reported to be the cause of increased sulfide levels resulting from the decomposition of organic matter. As more dams are being built, a better understanding of the impact of sulfide on indigenous species is required. In Sarawak, Tor tambroides is a highly valuable and sought after species which is facing declining population. This study aimed to determine the behavioral responses and mortality of juvenile T. tambroides exposed to sulfide. The three exposure experiments were gradual sulfide exposure, gradual sulfide exposure under lowering DO and gradual sulfide exposure under lowering pH. A modified flow-through design was used to expose the juveniles in containers to sulfide of different concentrations. Actual total sulfide in containers was determined according to standard method. During the duration of the experiment, behavioral responses, DO and pH were monitored. Experimental results show that negative controls recorded no behavioral response and no mortality was observed in all control experiments. However, under all sulfide exposure experiments, the juveniles displayed at least one behavioral response in the progression of huddling together, aquatic surface respiration, loss of equilibrium and turning upside down except for the gradual sulfide exposure experiment where no response was observed with the lowest total sulfide concentration tested (82 µg L-1). For all three exposure experiments, faster responses and mortalities were observed when the concentration of sulfide increased. The LC50 at 6th hour of exposure was estimated to be 306 µg/L total sulfide (138 µg L-1 H2S) at 95% confidence level. Sulfide toxicity was found to be highly related to the decreasing DO and pH levels attributable to intensifying toxicity which led to mortality.